A killer's Christmas in Wales : a Penny Brannigan mystery - Duncan, Elizabeth J. (Duncan, Elizabeth J. Penny Brannigan mystery., 2011)
Penny Brannigan and her business partner, Victoria Hopkirk, are absorbed with the grand opening of their new spa. Meanwhile, an American stranger, Harry Saunders, arrives in town and sweeps widow Evelyn Lloyd off her feet. Some suspect Saunders is taking advantage of Evelyn, so it's no surprise when he goes missing with a healthy chunk of Evelyn's money and is eventually found dead outside Conwy Castle.